2023
DOI: 10.3390/su15021474
|View full text |Cite
|
Sign up to set email alerts
|

Factors Indicating Media Dependency and Online Misinformation Sharing in Jordan

Abstract: Although social media is a vital platform in our life, it is blamed for poor efforts to moderate content included mis/disinformation and fake news. This could have an impact on its legacy and on sustainability in society in the long term. This research examined the role of social media in spreading misinformation during the COVID-19 outbreak in Jordan. A cross-sectional design questionnaire (350 responses) was used. The results revealed that social media played a key role in updating users with COVID-19 inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…This research used quantitative methodology to analyze the causal relationship between independent, dependent, and outcome variables (Al Dulaimi & Al Hindawy, 2023;Alsuwaidi, 2023;Pasha et al, 2023;Sarwar et al, 2023). Target population of this research was the young population including college students from Oman (Dhofar University and University of Technology and Applied Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…This research used quantitative methodology to analyze the causal relationship between independent, dependent, and outcome variables (Al Dulaimi & Al Hindawy, 2023;Alsuwaidi, 2023;Pasha et al, 2023;Sarwar et al, 2023). Target population of this research was the young population including college students from Oman (Dhofar University and University of Technology and Applied Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…Sharing news without authentication could contribute to the proliferation of fake news, which exerted a negative impact on others and damaged one's reputation (Apuke & Omar, 2020b). Studies also found that reducing exposure to social media news and the time spent on social media were effective ways for curbing fake news sharing about COVID-19 (Habes et al, 2023;Wu, 2022). Excessive social media dependency can cause information overload for users, and negative emotions of anxiety and worry make people more susceptible to fake news.…”
Section: Driving Factors Of Covid-19 Related Fake News Sharing On Soc...mentioning
confidence: 99%
“…Consumption of online media directly indicates an increasing dependency on digital platforms, meaning that users depend on online media for various reasons and purposes, although entertainment remains the dominant factors, educational and informational support and assistance is the other powerful factors accelerating dependency online media among the young generation. (Habes et al, 2023) said that online media dependence is caused by the student personality, awareness and emotional stability, student demographic conditions. The dimensions used to measure online media dependency are, first; spend time using digital media platforms.…”
Section: Online Media Addictionmentioning
confidence: 99%